Primary school teachers' knowledge and attitude regarding traumatic dental injuries - Simona Daupare; Julija Narbutaite (Wolters Kluwer Medknow Publications, 2020)
Aim: According to the WHO, 16%-40% of children aged 6-12 years experience dental traumas. Long-term treatment success depends on immediate emergency care and early professional management after the injury occurred. The primary school teachers can play a crucial role in managing traumatic dental injuries (TDIs) because they are often in proximity to children and often need to assist when dental trauma occurs. The aim of the present study was to assess primary school teachers' knowledge and attitude regarding TDI and describe their behavior in emergency situations. Materials and Methods: A four-part anonymous questionnaire comprised questions on demographic data, attitude, knowledge toward TDI, and behavior in case of accident and self-assessment questions were distributed among 147 teachers from 16 schools. The data were obtained from 106 participants (72.1%). The Kruskal-Wallis and independent t-tests served for statistical analysis. Results: More than half of teachers (56.6%) have witnessed TDI. Almost all respondents (94.3%) indicated that in case of dental trauma is important to take emergency management as soon as possible. However, two-thirds of them (75.5%) thought that teachers cannot provide appropriate emergency management in case of TDI. In addition, teachers had little knowledge regarding TDI and the proper emergency management: 91.3% of participants do not know the right storage media for the avulsed tooth, 40.6% have thought that tooth replantation is impossible, and 17.1% would throw an avulsed tooth away, when it fells on the ground. Conclusion: The study revealed inappropriate knowledge and attitude regarding TDI among primary school teachers and their behavior in first-aid management.